Prognostic changes after sudden deafness in patients with inner ear malformations characterized by LSCC: a retrospective study - Chen, Lei; Dai, Qinglei; Gao, Xin; Hu, Na; Sun, Xiao; Wang, Haibo; Wang, Mingming (Frontiers in Neurology, 2023)
Introduction This study aimed to investigate the clinical features and prognosis of sudden sensorineural hearing loss in patients with lateral semicircular canal (LSCC) malformation. Methods This study enrolled patients with LSCC malformation and sudden sensorineural hearing loss (SSNHL) who were admitted to Shandong ENT Hospital between 2020 and 2022. We collected and analyzed data on examinations of audiology, vestibular function, and imaging records of patients and summarized the clinical characteristics and prognosis of these patients. Results Fourteen patients were enrolled. Patients with LSCC malformation was noted in 0.42% of all SSNHL cases during the same period. One patients had bilateral SSNHL and the rest had unilateral SSNHL. Of them, eight and six patients had unilateral and bilateral LSCC malformations, respectively. Flat hearing loss was noted in 12 ears (80.0%) and severe or profound hearing loss was noted in 10 ears (66.7%). After treatment, the total efficacy rate of SSNHL with LSCC malformation was 40.0%. Vestibular function was abnormal in all patients, but only five patients (35.7%) had dizziness. There were statistically significant differences in the vestibular functions between patients with LSCC malformation and matched patients without the malformation hospitalized during the same period (p < 0.05). Conclusion Patients with SSNHL and LSCC malformation had flat-type and severe hearing loss and worse disease prognosis compared to those with SSNHL without LSCC malformation. Vestibular function is more likely to be abnormal; however, there was no significant difference in vestibular symptoms between patients with and without LSCC malformation. LSCC is a risk factor for the prognosis of SSNHL.